Health problems and help-seeking activities of methadone maintenance clients at Auckland Methadone Service (AMS): potential for community pharmacy service expansion? - Wheeler Amanda; Sheridan Janie; Walters Carina (BMC, 2005)
Abstract Background In general the health of methadone clients has been found to be poorer than that of the general population. In New Zealand specialist drug services are not funded to provide primary healthcare services. Many health conditions could potentially be managed by community pharmacists who have frequent contact with this client group. This study sought to explore the health problems suffered by methadone clients, who they sought help from, and the potential for greater involvement of pharmacists. Methods Self-completion questionnaire of methadone maintenance clients managed in specialist care in Auckland, New Zealand. Results The most common health problem experienced by these clients in the past three months was sweating (70.0%), and more than half of the respondents also reported experiencing headache, fatigue and depression. The least frequently experienced conditions were hay fever (12.9%) and abscesses (12.1%). Respondents indicated that the top three choices from whom they would seek help were GP (56.7%), the client's partner (31.6%) and community pharmacists (27.9%). Barriers to seeking help from pharmacists included issues around cost, perceptions of pharmacist knowledge and skills, privacy and confidentiality. Conclusion Methadone clients in this study indicated that they suffered a number of general health problems, and in many cases were likely to seek help from a GP or their own partner, before seeking help from pharmacists. However, for over one quarter of respondents the pharmacist was in the top three from whom they would seek advice. Any barriers towards consulting pharmacists, in the main seem to be resolvable.